It is a matter of convenience: why welfare technologies have become domesticated in Swedish eldercare - Susanne Frennert; Katrin Skagert; Anna Williamsson (BMC Health Services Research)
Abstract Background The use of welfare technology is gaining ground in municipal eldercare and is increasingly being integrated into everyday routines. However, the meanings that eldercare personnel attach to welfare technology in the care of older recipients, and thus the domestication of welfare technology, remain largely underexplored. This study explores how eldercare personnel understand and ascribe meanings to welfare technologies in their daily work, with the aim of understanding their domestication. Methods The empirical material comprised 181 photographs, each paired with corresponding text, from 61 participants across four municipalities in southern Sweden. The empirical material was thematically analysed, focusing on different categories of welfare technologies and their ascribed meanings. In our coding “convenience” and at times “inconvenience” were interpreted as recurrent patterns. Their repeated presence across various contexts and the meanings ascribed to different welfare technologies prompted deeper interpretive engagement, leading us to adopt it as a key theme. In the final step, the codes were synthesised through the lens of “convenience” to better understand the meanings participants attached to welfare technology in eldercare work. Results The participants ascribed meanings to welfare technology that resonate with broader societal and cultural understandings of technological solutionism, while aligning with national policies promoting welfare technology as a means of supporting safety, activity and independence for older adults. Welfare technology was often understood as both convenient and an act of care. Our analysis uncovered different dimensions of “convenience”, which we labelled as: “remote surveillance convenience”, “logistics convenience”, “communication convenience”, “safety convenience”, “comforting convenience” and “activation convenience”. Yet, in some cases, welfare technology was also seen as a hindrance to care, being inconvenient due to its inflexibility, technical difficulties and the tendency to create duplicate tasks. Conclusion This paper contributes to a deeper understanding of the domestication of welfare technology in eldercare. Our study found that eldercare personnel engage with and interpret welfare technologies by ascribing meanings related to perceived convenience — a concept not widely explored in this context. Welfare technologies were often seen as convenient substitutes for physical proximity and relational care, such as “remote surveillance convenience” through cameras and “comforting convenience” via robotic pets. However, convenience, while central to the participants’ experiences, should not be understood as inherently “good” or positive but as part of the domestication process, shaped by socio-technical contexts and the political economy of eldercare, which prioritises effectiveness and efficiency. By shedding light on these dynamics, our study examines how the domestication of welfare technology is shaped by and reinforces broader discourses of technological solutionism, raising questions about its long-term impact on care practices.